Competition Patterns and their Effect on the Prices of Expired Patent Medicines in Mexico: the Case of Antibiotics - Rios Nequis, Eric Israel (2018)
The expired patent pharmaceutical market has an interesting behavior with respect to its market structure, changing from a monopolistic case derived from patent protection to an oligopoly, where the company that had such protection (pioneer) holds the dominant role through a Stackelberg behavior, which applies strategies of product differentiation in a segmented market, which is not very sensitive to change in prices and which retains a non-negligible share. In this sense, other companies that manufacture generics with a commercial brand, penetrate the market with a similar strategy with differentiated products and lower prices. This is due to the prestige and competitive positioning of the product with recent expiration. Consequently, little differentiated products are offered that compete for economic prices, which obtain a considerable market penetration in a price-sensitive segment. This behavior explains the variation in drug prices. The strategies that stand out are the dosages, the prestige of the product through a brand and the line of presentations, looking for imperfect price behavior and similar to the generic paradox, where public policy has the capacity to reduce such fluctuations in the search for economic options for the population.